Small- to medium-scale deep syngas purification: Biomass-to-liquids multi-contaminant removal demonstration. (May 2021) - Frilund, Christian; Tuomi, Sanna; Kurkela, Esa; Simell, Pekka
Abstract: The complete and economic removal of harmful components from biomass gasification-based syngas is a major challenge. A final gas cleaning concept for syngas purification to catalytic synthesis quality was developed as an alternative to organic-solvent scrubbing technologies. The motivation is to present smaller-scale BTL processes with a potentially lower-capex gas cleaning solution. The purpose of this study was to realize and validate the final gas cleaning concept in a real syngas environment and to study longer-term performance of deep gas cleaning. Two successful PDU-scale campaigns in complete biomass-to-liquids production chain were performed. A total on-stream time of 163 h was realized in syngas generated from residual woody- and agro-biomasses, with coupled gas feeding to Fischer-Tropsch synthesis. For S-species removal the final gas cleaning featured a novel hybrid of activated carbon- and ZnO-based bed materials. NH3 and partial CO2 removal was achieved by pressurized water scrubbing. The campaigns employed extensive continuous and non-continuous analysis techniques for the study of syngas impurities such as H2 S, COS, NH3, HCN, HCl, benzene and tar. The final gas cleaning process demonstrated flexible deep removal of syngas contaminants of all tested biomass origins, thus achieving similar or better purification levels as conventional wet-scrubbing technologies. The cleaned gas was therefore suitable for catalytic synthesis purposes, demonstrating the technical feasibility of the new final cleaning process in conjunction with optimized hot gas cleaning. Highlights: Experiments with full biomass-to-FT process configuration for investigation of deep gas cleaning. The simplified final gas cleaning intended for smaller-scale utilized water scrubbing and adsorption-based removal steps. Extensive analytical techniques were employed for the determination of trace syngas impurities. The hybrid activated carbon- and ZnO-based process achieved gas quality suitable for feeding to catalytic synthesis. Technical feasibility of the final cleaning in conjunction with hot gas cleaning was established.